Analysis of Company Bankruptcy Based on Cash Flow Statement at PT Visi Media Asia Tbk - Sukanta, Tuntun Ariadi; Sudirman, Dudi (AL-IBANAH, 2025)
This research entitled "Analysis of Company Bankruptcy based on Cash Flow Statement at PT Visi Media Asia Tbk" analyzes the possibility of the company bankruptcy using the cash flow statements in the period of 2018 until 2023. Utilizing a qualitative descriptive method and case study approach, the analysis focuses on seven financial ratios: In addition, from the balance sheet and income statement perspective, Current Liability Coverage Ratio (CLCR), Cash Flow Coverage of Interest (CFCOI), Operating Cash Flow Margin (OCFM), Operating Cash Flow Return on Total Assets (OCFROA), Quality of Earnings (QOE), Quick Ratio (QR), and Years Sales Growth (YSG) have been used. Significant liquidity issues and an inability to meet short-term liabilities seen with all ratios go down. Low CLCR and QR indicate difficulty of current liabilities to cover and CFCOI decline indicate debt interest payments worries. A negative YSG is related to a reduction in market competitiveness. The research concludes that PT Visi Media Asia Tbk should apply strategic measures such as debt restructuring and operational improvement, in order to mitigate risks bankruptcy and improve financial health, and in order to ensure future sustainability.